Nursing Consultation in Primary Health Care: Care for people with chronic cardiometabolic diseases - Maria Clara Moreira Matias; Uiara Aline de Oliveira Kaizer; Thaís Moreira São-João (Universidade Federal de Santa Maria, 2021)
Objective: to design a nursing consultation instrument for people with high blood pressure and/or type 2 diabetes mellitus being followed up in Primary Health Care. Method: methodological study comprising two stages developed in a Basic Health Unit (BHS) in the interior of the state of São Paulo. Stage 1 was related to designing the instrument and validating its content with five judges. Stage 2 was related to pre-testing and evaluation of its measurement properties. The questionnaire was pre-tested with 30 people with high blood pressure and/or diabetes mellitus that attended the UBS. Results: the questionnaire had a high content validity index (CVI = 0,96) and moderate feasibility (considering the administration time). Conclusion: the instrument was adequate to the reality and need of primary health care in terms of content.